Arterial stiffness parameters associated with vitamin D deficiency and supplementation in patients with normal cardiac functions - Murat Sunbul; Altug Cincin; Mehmet Bozbay; Ceyhun Mammadov; Halil Atas; Ekmel Burak Ozsenel; Ibrahim Sari; Yelda Basaran (KARE Publishing, 2016)
Objective: Arterial stiffness parameters including pulse wave velocity (PWV) and augmentation index (AIx) are associated with increased risk of cardiovascular disease. A close relationship has been demonstrated between vitamin D deficiency and cardiovascular disease. The aim of the present study was to investigate effects of vitamin D deficiency and supplementation on arterial stiffness parameters in patients with normal cardiac functions. Methods: Study population consisted of 45 patients with vitamin D deficiency and normal cardiac functions. Median age (interquartile range) was 45.0 (12.00) years, and 33 patients were female. Patients were treated with oral administration of vitamin D3. Arterial stiffness parameters were evaluated using Mobil-O-Graph arteriograph system, which detected signals from the brachial artery before and after treatment. Results: Vitamin D levels significantly increased after treatment (9.0 [6.00] nmol/L vs 29.0 [11.50] nmol/L, p<0.001). No significant difference was observed among conventional echocardiographic parameters before or after treatment. Post-treatment PVW and AIx were significantly lower than baseline measurements (6.8 [1.55] m/s vs 6.4 [1.30] m/s, p<0.001 and 23.0 [22.00]% vs 31.0 [14.50]%, p<0.001, respectively). Baseline vitamin D levels significantly correlated with PWV (r=-0.352, p=0.018). Posttreatment vitamin D levels also significantly correlated with posttreatment PWV (r=-0.442, p=0.002) and AIx (r=-0.419, p=0.004). Multivariate linear regression analysis revealed no independent predictor of baseline log-transformed PWV. Conclusion: Vitamin D supplementation has beneficial effects on arterial stiffness. Arterial stiffness parameters may aid in the assessment of cardiovascular risk in patients with vitamin D deficiency.